European Union Backsliding in the Rule of Law: The Hungarian Case (Tema Central) - Arregui Acosta, Juan Diego (2023)
Hungary has experienced a backslide in its rule of law ever since Viktor Orbán modified its constitution. Orbán, characterized by right-wing populism, has been questioned not only for the way in which he has seized power, but also for the way in which he has favored his close friends and family. Orbán portrays a constitutional vision that has been described as illiberal constitutionalism, which he complements with the idea of an illiberal democracy, where a vision against integration prevails and rather enhances the idea of a national identity opposed to the values of the European Union as an excuse to disregard EU law. The responses of the European Union have varied, from political, judicial and economic sanctions, but seeing themselves trapped by the right to veto sanctions and the requirement of unanimity it would seem that there is no way out of the deterioration of the rule of law. Thus, the article analyzes different solutions, options, and possibilities in the face of the crisis of the rule of law and democracy in Hungary.